Religious Barriers to Birth Control Access - Olivier Marie; Esmée Zwiers (Institute of Labor Economics (IZA), 2023)
This paper presents new causal evidence on the "power" of oral contraceptives in shaping women's lives, leveraging the 1970 liberalization of the Pill for minors in the Netherlands and demand- and supply-side religious preferences that affected Pill take-up. We analyze administrative data to demonstrate that, after Pill liberalization, minors from less conservative areas were more likely to delay fertility/marriage and to accumulate human capital in the long run. We then show how these large effects were eliminated for women facing a higher share of gatekeepers – general practitioners and pharmacists – who were opposed to providing the Pill on religious grounds.
Keywords: I18; J12; J13; Z12; 330; birth control; religion; fertility; marriage; human capital; the Netherlands